The Hepatoprotective Effects of Ginsenoside from Ginseng: A Review of Molecular Mechanisms and Therapeutic Potentials - Taha, Seyed Reza; Fazlollahpour-Naghibi, Andarz; Zadeh, Mahdieh Shariat; Bagheri, Kimia; Youshanlouei, Hamed Rahmani; Mosaddeghi-Heris, Reza; Hejazian, Seyyed Sina; Khalaji, Amirreza; Alavi, Seyedeh Shaghayegh; Fattahi, Payam; Mehrtabar, Saba (Current Pharmaceutical Biotechnology, 2025)
Treatment of hepatic diseases presents a significant challenge due to their diverse nature. Ginsenosides, bioactive compounds derived from the root of Panax ginseng and widely used in traditional Chinese medicine, offer multifaceted protection to various organs in the body. Their versatile effects, including antioxidant, anti-inflammatory, anti-apoptotic and more, make them a promising approach for addressing hepatic disorders. This review explores the intricate molecular mechanisms and properties of ginsenosides in the prevention and treatment of liver ailments, from mild conditions to severe damage and liver fibrosis. Given the increasing prevalence of hepatic disorders, this article sheds light on the significant pharmaceutical potential of ginsenosides in the realm of hepatic disease management.
Keywords: alcoholic liver disease